A novel SAR reduction technique for implantable antenna using conformal absorber metasurface - Das, Soumyadeep; Mitra, Debasis; Chezhian, Arvind S.; Mandal, Bappaditya; Augustine, Robin (Frontiers in Medical Technology, 2022)
In this paper, a conformal absorber metasurface has been designed and used for reducing the specific absorption rate (SAR) of an implantable antenna. SAR reduction of implantable antennas is one of the significant design aspects to be considered for their use in modern-day healthcare applications. The introduction of the absorber metasurface restricts the back radiation of the antenna to control the SAR value. This technique decreases the maximum SAR value by 24% and also reduces the average SAR distribution significantly without affecting the desired antenna gain. A reduction in SAR value indicates the decrease in radiation absorption by human tissue, and thus, decreases the possibility of health hazards due to EM radiation. Later, this antenna-absorber system is designed as a capsule module for increased mobility and less-invasiveness. The redundancy of invasive surgery increases acceptance of the capsule module designs of implantable antennas and devices for various biomedical usages. In vitro testing of the fabricated prototype has been carried out inside a multi-layer porcine slab to verify the effectiveness of this unique SAR reduction technique.